THE EFFECT OF LEARNING VIDEOS ON THE CRITICAL THINKING ABILITIES OF SCIENCE STUDENTS ON THE MATERIAL OF INDONESIAN CULTURAL WEALTH IN GRADE 4 OF ELEMENTARY SCHOOL: PENGARUH VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA IPAS MATERI KEKAYAAN BUDAYA INDONESIA KELAS 4 SD - Thalia Azahra; Laili Rahmi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the effect of using video learning media on the critical thinking skills of fourth-grade students at UPT SD Negeri 017 Kualu in the subject of science. The background of the problem shows the low critical thinking skills of students, which are caused by less varied learning methods and minimal interaction in class. By using a quantitative approach through the experimental method of the One-Group Pretest-Posttest Design , this study involved 30 students as a sample. Data were collected through critical thinking ability test instruments (pretest and posttest) that have been tested for validity and reliability, and supported by qualitative data from observations and interviews. The results of the study showed a significant increase in students' average scores from 48.9 (pretest) to 74.8 (posttest). This increase was supported by a paired t-test, which produced a t-count value of 14.32, much greater than the t-table (2.045) with a significance value of 0.000 (p <0.05). Qualitative findings confirmed that video media successfully increased students' motivation, enthusiasm, and active participation in learning. Thus, this study proves that learning video media has a significant influence on improving students' critical thinking skills, and is able to create a more interactive and effective learning environment